Marcia - Steptoe, John, 1950- (New York : Viking Press, 1976)
A fourteen-year-old black girl living in the city tries to answer some very tough questions about life.
5.9
Young Adult
Young Adult
Keywords: Youth -- Conduct of life -- Fiction; City and town life -- Fiction